Studying in the United States: Language Learning Challenges, Strategies and Support Services - Wolf, Debra M; Phung, Linh (Journal of International Students, 2019)
A case study was conducted to explore the experiences of Chinese nurses when completing a graduate nursing degree taught in English (as a second language) in the United States over a one-year period. The study explored language, academic, and social challenges perceived by the students, strategies used to overcome challenges, and academic support services designed to help students succeed in their studies. Survey data were collected at three different points in time, and three interviews were conducted with each participant. The study identified participants’ difficulty with academic writing, mixed experiences with speaking, moderate to high levels of strategy use, and appreciation of the support services offered. The study offered implications for improvements in pedagogies and programming for international students.